1987
DOI: 10.1203/00006450-198704000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Correlates of Renal Growth Arrest in Neonatal Partial Ureteral Obstruction

Abstract: ABSTRACT. To investigate the morphologic correlates of decreased renal blood flow and growth arrest resulting from chronic partial ureteral obstruction in the neonate, guinea pigs were subjected to unilateral ureteral constriction within the first 2 days of life and were studied at 3 and 8 wk of age. Severity of histologic changes in the obstructed and intact contralateral kidney was assessed by light microscopy. Morphometric glomerular measurements were made using a computerized tracing device. Since contrala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0
2

Year Published

1990
1990
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 15 publications
3
22
0
2
Order By: Relevance
“…In the newborn guinea pig, Taki et al [20] found a reduction in dry KW of 20% after 5 weeks, but none in wet KW; histology was not studied. Chevalier et al [21,28] found that both wet and dry KW were reduced by 30-40% after 8 weeks. They observed a moderate degree of tubular dilatation and atrophy, of interstitial fibrosis and of sclerosis in 30% of the glomeruli.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In the newborn guinea pig, Taki et al [20] found a reduction in dry KW of 20% after 5 weeks, but none in wet KW; histology was not studied. Chevalier et al [21,28] found that both wet and dry KW were reduced by 30-40% after 8 weeks. They observed a moderate degree of tubular dilatation and atrophy, of interstitial fibrosis and of sclerosis in 30% of the glomeruli.…”
mentioning
confidence: 97%
“…was decreased by about 95%, but glomerular number was not affected. Chevalier et al [21,28] found that GFR was decreased by about 95%, renal blood flow (RBF) by 85% and glomerular number by 35%. The large differences found between our results and those of the groups are probably due to the different degrees of obstruction, as shown by the above-mentioned ureteral resistance figures [20,[23][24][25] Tubular Functions.…”
mentioning
confidence: 99%
“…Differences between parameters were evaluated by using analysis of variance according to the model X ijkl = u + Gi + Tj + SI + Bk(ij) + GT ij + GS il + GTS ijl + SB kl(ij). u is a constant, Gi the treatment factor (experimental or control/spontaneously hy dronephrotic animals), Tj the time factor (7,8,9,15 or 21 weeks of age), SI the side (left or right kidney), Bk(ij) the individual biological variation within each group. GT ij, GS il, GTS ijl and SB kl(ij) are the different interaction terms.…”
Section: Methodsmentioning
confidence: 99%
“…A reduction in the number of glomeruli has been seen after the creation of a com plete obstruction in rabbit fetuses (which appears almost immediately), but not after obstruction in newborn rab bits [6] or adult dogs [7], Partial obstruction, which should be less harmful, led to a reduction in the number when it was created in newborn rats [2] and guinea pigs [8] or (again rather quickly) in weanling rats [4], The morphology of glomeruli is obviously resistant; shrink age and sclerosis have not been seen until after months of obstruction [9], In infant kidneys, no reduction in number was recorded [10]. However, microstructural changes have been observed, such as lesions suggestive of type II cystic kidneys (early ampullary inhibition) in fetuses [11] and focal glomerulosclerosis in infants and older children [12,13] together with inflammatory changes [14].…”
mentioning
confidence: 99%
“…In the post ischemic kidney, on the other hand, ET was found to be dominating [7], In previous studies of ureteric obstruction, Josephson and co-authors [8][9][10][11] and other researchers [12,13] found a moderate reduction in glomerular number, not confined to any specific renal zone [9]. Glomeruli have been found to degenerate, but this does not develop until after weeks or months and is surprisingly heterogeneous [14][15][16][17], One reason for these changes might be a reduc tion in blood flow. However, this does not cease totally [18], and some filtration may continue for a long period, the filtrate being drained via pyelo-renal, pyelo-venous and pyelo-lymphatic exits [19,20] Clinical ureteric obstruction is usually a congenital dis order.…”
Section: 01) the Intact Kidney Was Similar To The Corresponding Comentioning
confidence: 99%